Diversity, knowledge, and valuation of plants used as fermentation starters for traditional glutinous rice wine by Dong communities in Southeast Guizhou, China - Jianwu He; Ruifei Zhang; Qiyi Lei; Gongxi Chen; Kegang Li; Selena Ahmed; Chunlin Long (BMC, 2019)
Abstract Background Beverages prepared by fermenting plants have a long history of use for medicinal, social, and ritualistic purposes around the world. Socio-linguistic groups throughout China have traditionally used plants as fermentation starters (or koji) for brewing traditional rice wine. The objective of this study was to evaluate traditional knowledge, diversity, and values regarding plants used as starters for brewing glutinous rice wine in the Dong communities in the Guizhou Province of China, an area of rich biological and cultural diversity. Methods Semi-structured interviews were administered for collecting ethnobotanical data on plants used as starters for brewing glutinous rice wine in Dong communities. Field work was carried out in three communities in Guizhou Province from September 2017 to July 2018. A total of 217 informants were interviewed from the villages. Results A total of 60 plant species were identified to be used as starters for brewing glutinous rice wine, belonging to 58 genera in 36 families. Asteraceae and Rosaceae are the most represented botanical families for use as a fermentation starter for rice wine with 6 species respectively, followed by Lamiaceae (4 species); Asparagaceae, Menispermaceae, and Polygonaceae (3 species respectively); and Lardizabalaceae, Leguminosae, Moraceae, Poaceae, and Rubiaceae (2 species, respectively). The other botanical families were represented by one species each. The species used for fermentation starters consist of herbs (60.0%), shrubs (23.3%), climbers (10.0%), and trees (6.7%). The parts used include the root (21.7%), leaf (20.0%), and the whole plant (16.7%). Findings indicate a significant relationship between knowledge of plants used as fermentation starters with age (P value < 0.001) and educational status (P value = 0.004) but not with gender (P value = 0.179) and occupation (P value = 0.059). The species that are most used by informants include Pueraria lobata var. montana (Lour.) van der Maesen (UV = 1.74; Leguminosae), Actinidia eriantha Benth. (UV = 1.51; Actinidiaceae), Oryza sativa L. var. glutinosa Matsum (UV = 1.5; Poaceae). Conclusion This study highlights that while most of the Dong informants continue to use a diverse range of plants as a fermentation starter for brewing glutinous rice wine, knowledge of these plants is being lost by the younger generations. Documentation of traditional ethnobotanical knowledge and outreach is thus needed to conserve biocultural diversity in the rural Dong communities in southern China.